HUBUNGAN KOPING STRES DENGAN KEPATUHAN MINUM OBAT PADA PENDERITA TUBERKULOSIS PARU - Friska Ernita Sitorus; Dewi Tiansa Barus (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2018)
Pulmonary Tuberculosis (TB) is an infectious disease that still has became theworld concern. In Indonesia, pulmonary tuberculosis is still major communityhealth problem eventhough the goverment have already develop Tuberculosis programsince decade ago. The purpose of this research is to describe factors contributing to pulmonary tuberculosis through general characteristic of the pulmonary Tubeculos is patients and their environmental especially housing condition.The aims of Reseach to know the relationship of coping stress with adherence to Medication in people with Tuberculosis in Delitua Sub district health centers Delitua Deli Serdang district the year 2017. The study is Observational, analytic approach of cross sectional. The subject of research was Pulmonary Tuberculosis sufferers in the region Delitua, County Health Center Deliserdang. The Data of obtained by the used of questionnaires and direct observations in the neighborhood Health Center. Sampling of the techniques, namely the minimum number of samples with 61 samples. The data using computer programs with the chi-square test with a significance level of 95% (? = 0.05) value p = 0.001. The results of the data analysis Univariate statistics for trials with Koping stress indicate that the average sufferer of Tuberculosis are at categories de-stress kopingAdaktif 70.5%,as for compliance with medication is at a category i.e. 82.0% Obedient, Chi-square test results Showed there is Relationship stress Compliance with the Koping medication (0.001). The conclusions of this Reasech showed that stress Koping have relationships with Medication Compliance.